EFEKTIVITAS PROBLEM SOLVING THERAPY MENGURANGI STRES DAN MENINGKATKAN KEMAMPUAN PROBLEM SOLVING PADA WANITA YANG PERNAH MENGALAMI KEKERASAN DALAM RUMAH TANGGA - Lasutri Tama, Mulia Marita (Jurnal Ilmiah Psyche, 2018)
The purpose of this study is to design a therapy module and determine the therapeutic effectiveness of Problem Solving Therapy which is an approach based on cognitive behavior that focuses on training attitudes and effective problem solving skills. The approach used in this study is a mixed method that involves collecting qualitative and quantitative data. Qualitative data used in this study are interviews, observations, and daily report self-problems, while the quantitative data are in the form of DASS questionnaires (Depression, Anxiety, Stress Scale) and Problem Solving Test. The results showed that there were significant differences between the results of the pre test and post test. In addition, there are also changes in the cognitive, emotional and behavioral areas, such as subjects who are able to think positively about the day-to-day situations, events, and problems so that they also affect the emotions and behavior of subjects such as subjects more calm and more able to control his emotions when facing situations, events, and everyday problems. Thus the therapy used in this study is Problem Solving Therapy effective for reducing stress and improving problem solving abilities in individuals who have experienced domestic violence.